1994
DOI: 10.1029/93ja02771
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of phase space distributions of storm time proton ring current

Abstract: We use results of guiding-center simulations of ion transport to map phase space densities of the stormtime proton ring current. We model a storm as a sequence of substorm-associated enhancements in the convection electric field. Our pre-storm phase space distribution is an analytical solution to a steady-state transport model in which quiet-time radial diffusion balances charge exchange. This pre-storm phase space spectra at L~2-4 reproduce many of the features found in observed quiet-time spectra. Using resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(166 citation statements)
references
References 47 publications
4
161
0
Order By: Relevance
“…We consider the proton loss due to charge exchange (see Chen et al [1994] for details). For electrons, we consider losses due to wave-particle interactions (see Liu et al [2003] for details).…”
Section: Simulation Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider the proton loss due to charge exchange (see Chen et al [1994] for details). For electrons, we consider losses due to wave-particle interactions (see Liu et al [2003] for details).…”
Section: Simulation Model Descriptionmentioning
confidence: 99%
“…The LANL/ MPA data were provided by H. Korth, and explained by Korth et al [1999]. The electron [Albert, 1994] and proton [Chen et al, 1994] initial conditions are taken from theoretical solutions of steady state transport equations, and normalized with quiet time boundary conditions. We use averaged LANL/MPA data for Kp = 1 as the quiet time boundary conditions to normalize our initial conditions, and for Kp = 3 as the stormtime boundary conditions.…”
Section: Simulation Model Descriptionmentioning
confidence: 99%
“…At least four groups are working at present along this path. They are located at the University of Michigan, the Aerospace Corporation, NASA-Goddard Space Flight Centre, and Rice University (see Chen et al, 1994 for a review of these works). Differences between their models are mainly related to a different selection of aspects of the problem that are treated at a state-of-the-art level or neglected.…”
Section: Ring Current Modelsmentioning
confidence: 99%
“…Simulations not only complement the observational studies, but are in fact essential to the understanding of ring current and storm dynamics. Among the efforts regarding the "substorm-induced electric field" question, we should mention Chen et al (1994), who used spike-like enhancements of the convection electric field to simulate the effect of individual substorms, and Fok et al (1996), who used an iductive localised electric field, tied to successive cycles of stretching and diplarisation of the Tsyganenko model magnetic field. The results of both efforts suggested that the substorm contribution was subtle, and possibly negative to the development of a ring current.…”
Section: Ring Current Growth and Substorm Influencementioning
confidence: 99%
“…The first enhancement in the ring current may be due to the magnetospheric convection driven by the southward IMF (e.g., McPherron, 1997), while the second ring current enhancement may be due to the substorm-associated accumulation of a new O + population. This second growth of the ring current must be driven by "highly fluctuating" electric fields (e.g., Chen et al, 1994), resulting from substorm expansions. It is well known that toward the end of the main phase of magnetic storms, the occurrence of intense substorms is very frequent and that the O + energy density in the inner magnetosphere is strongly correlated with these substorm activities (Daglis et al, 1994).…”
Section: Ionospheric Origin Of Ring Current Particlesmentioning
confidence: 99%